Integrating Digital Cognitive Mapping into Speaking Instruction: A Quasi-Experimental Study with Indonesian EFL Students - Hamdan Hamdan; Agus Triyogo; Ayu Oktaviani (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2025)
Background of study: Speaking is a fundamental component of communication skills for English as a Foreign Language (EFL) students. Nevertheless, many learners encounter difficulties in expressing ideas fluently and coherently in oral communication. These challenges highlight the need for instructional strategies that facilitate idea generation, organization, and delivery through technology-enhanced learning environments.Aims: This study aims to examine the effect of integrating digital cognitive mapping into speaking instruction on the speaking performance of Indonesian EFL university students.Methods: A quasi-experimental pretest–posttest control group design was employed involving 44 students enrolled in an English Language Education program. The participants were divided into an experimental group (n = 22) and a control group (n = 22). The experimental group received speaking instruction supported by digital cognitive mapping tools, while the control group engaged in conventional speaking activities without cognitive or digital mapping. Students’ speaking performance was assessed using standardized speaking rubrics, and the data were analyzed using descriptive and inferential statistics.Result: The results indicated that the experimental group showed a statistically significant improvement in speaking scores from pretest to posttest, whereas the control group demonstrated only a slight and non-significant gain. In addition, the experimental group significantly outperformed the control group on the posttest.Conclusion: The study concludes that digital cognitive mapping is an effective instructional tool for enhancing EFL students’ speaking performance, particularly in planning, organizing, and delivering oral texts. These findings support the integration of technology-enhanced, learner-centered speaking activities using visual knowledge-organization tools in higher education contexts.